If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + 6x = 97 Solving 1 + 6x = 97 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 6x = 97 + -1 Combine like terms: 1 + -1 = 0 0 + 6x = 97 + -1 6x = 97 + -1 Combine like terms: 97 + -1 = 96 6x = 96 Divide each side by '6'. x = 16 Simplifying x = 16
| -2+12=0 | | x/2+14 | | 2(x+8)+3x=7+2x | | 9y-(6y+19)=6-(3y-4) | | 15-2x=3y | | 6x-8=6(x+7) | | -4y-11=4r+21 | | 0=7(a+1) | | (y^2-6y+8)/(y^2+3y-28) | | -7x-10=53 | | 5p+12=2t | | 3-2B+B+4+B=57 | | 138-x=45 | | -2x+4=-3 | | -9-3(2m-1)=-18 | | 9y+x=8 | | 75+45x=255 | | -5=-6+b/3 | | 120-4(8x-22)=16 | | x+x+54=90 | | 2x+1/5=3x+2/5 | | 15=50 | | 5(-1+-1y)+y=-13 | | 5(-1+-1y)+y=-31 | | 9x^2-6x+37=0 | | -16t^2+48t+4=0 | | a^2x^2+2ax-8=0 | | k/11=6 | | 140=(8x+4)+(3x+4) | | J(-13)=4(-13)+11 | | -16t^2+48+4=0 | | -10=-8+r/6 |